2017
DOI: 10.3389/fpls.2017.00802
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Trees in a Subtropical Forest Respond to Drought Mainly via Adjusting Tissue Soluble Sugar and Proline Content

Abstract: It is well-known that drought has considerable effects on plant traits from leaf to ecosystem scales; however, little is known about the relative contributions of various traits within or between tree species in determining the plant’s sensitivity or the tolerance to drought under field conditions. We conducted a field throughfall exclusion experiment to simulate short-term drought (∼67% throughfall exclusion during the dry season from October to March) and prolonged drought (∼67% throughfall exclusion prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 66 publications
3
13
0
Order By: Relevance
“…Therefore, extending the dry season did not result in water stress that would restrict plant growth and N uptake. Moreover, a previous study conducted in the same forest as this study reported that extending the dry season increased the leaf N content of the dominant species (S. superba and M. macclurei; Kuang et al, 2017). This suggests that extending the dry season in this studied subtropical forest does not restrict plant N uptake, but may stimulate it by increasing the concentration of soil inorganic N.…”
Section: Responses Of Soil N Dynamics To Extended Dry Seasonsupporting
confidence: 59%
“…Therefore, extending the dry season did not result in water stress that would restrict plant growth and N uptake. Moreover, a previous study conducted in the same forest as this study reported that extending the dry season increased the leaf N content of the dominant species (S. superba and M. macclurei; Kuang et al, 2017). This suggests that extending the dry season in this studied subtropical forest does not restrict plant N uptake, but may stimulate it by increasing the concentration of soil inorganic N.…”
Section: Responses Of Soil N Dynamics To Extended Dry Seasonsupporting
confidence: 59%
“…To reduce osmotic potential, plants often accumulate osmolytes such as proline, soluble sugars, and amino acids ( Kuang et al, 2017 ; Li et al, 2020 ). Parallel with Ψ pd and Ψ md , N addition and drought increased the NSC concentrations, which was evidenced by significant increases in soluble sugar and starch in the leaves or xylem for both O. pinnata and S. superba .…”
Section: Discussionmentioning
confidence: 99%
“…The solution was then centrifuged at 8,000 g at 25°C for 10 min. The resulting supernatants were combined and analyzed using the anthrone–sulfuric acid method ( Kuang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%